TOPICAL AGENTS USED BY HOUSEWIVES AS FIRST AID BURNS IN SLEMAN DISTRICT YOGYAKARTA INDONESIA - Nofiyanto, Muhamat; Nirmalasari, Novita (Universitas Respati Yogyakarta, 2020)
Burns are the most potential type of injury experienced by housewives. The use of topical agents for first aid burns that are inappropriate or not standardized can worsen the condition. This purpose of this study was to determine the used of topical first aid agents for burns to housewives. This was a descriptive observational study, included 84 respondents were selected using simple random sampling technique with the criteria of housewives who are still actively doing activities in the kitchen, as well as other household activities. Questionnaire was used to collecting the data. The data was analysis descriptively. The average age of respondents was 43.63 years (SD 11.46), most burns occurred while cooking 61 (73.5%), the most common cause was exposure to hot oil 54 (64.3%), the highest frequency was less than 5 times a year 50 (60.2%), most suffered injuries in the hand area of 49 (59%), with the most injuries being 1-3 cm 42 (50.6%), the wound condition was mostly 58 (69.9%), and recovered well, with little trace of 65 (78.3%). The most risky household activity is cooking 69 (82.1%). Nearly all 82 respondents (97.6%) practiced the use of topical agents for burns, with the most use being toothpaste 34 (41.5%), while the herbs commonly used were Aloe vera, as many as 19 (23.2% ). There is still the practice of using topical agents for burns that have not been standardize /not quite right on housewives in the Sleman district.